Web development with the Mac - Vegh, Aaron (Indianapolis, Ind. : Wiley Pub., 2010)
"Create and deploy striking Web sites and apps on a Mac for your own business or for clients using the essential techniques in this focused guide. While most Web site how-tos are geared toward either designers or programmers, this detailed book covers both aspects, helping you develop the complete skill sets that you'll need professionally. Tap all of the out-of-the-box perks that Apple has to offer for Web development with these techniques and insights from a seasoned Mac Web developer. Turn your design and development skills into marketable assets with this essential guide for Apple users"--Resource description page.
pt. 1. Internet infrastructure -- pt. 2. Client-side Development -- pt. 3. Web design -- pt. 4. Server-side development.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Web site development; Macintosh (Computer); Sites Web; Macintosh (Ordinateur); COMPUTERS -- Web -- Web Programming; Web site development; Macintosh (Computer); Macintosh (Computer); Web site development